Pelatihan Digital Marketing untuk Meningkatkan Daya Saing UMKM di Era Digital: Studi pada Pelaku UMKM Kampung Dayun, Kecamatan Dayun, Kabupaten Siak - N, Nurjanah; Insani, Dhia Nur; Shofa, Gaetsa Zahira; Ayun, Qurrata; Putri, Zahara Ananda; Vaherni, Dwi Rian; Maulana, M. Razif; Ain, Nurul; Suhendra, Zhafira; Iqbal, Nabilul; Ravi, Muhamad (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
In the rapidly developing digital era, digital marketing has become an urgent need for Micro, Small, and Medium Enterprises (MSMEs) to survive and compete in an increasingly competitive market. MSMEs who do not adapt to technology in the digital era will risk losing their competitiveness, especially when their competitors succeed in optimally integrating digital marketing strategies. Digital marketing training is a strategic step in facing marketing challenges in the digital era, especially for MSMEs in rural areas. This article discusses the implementation of digital marketing training for MSMEs in Kampung Dayun, Dayun District, Siak Regency, as part of efforts to increase the competitiveness of local businesses. The method of implementing this activity is carried out using the workshop method. The main objective of this training is to equip MSMEs with knowledge and skills in utilizing digital technology to expand the market, increase marketing efficiency, and optimize regional economic potential. The results of the activity showed an increase in MSMEs' understanding of digital marketing strategies, such as the use of social media and e-commerce platforms. In addition, this training also encourages active community participation in promoting local products creatively and innovatively. It is expected that this digital marketing training can be a new forum for UMKM actors in Kampung Dayun to gain new knowledge to develop their businesses in this digital era.